Location and seed transmission of fungi in discoloured seeds of hybrid rice - and M.P. PANDEY2, VACHSPATI PANDEY1, V.K. AGARWAL1 (Indian Phytopathology, 2002)
The seedborne fungi and seed discoloration of freshly harvested seeds of hybrid rice were investigated. Alternaria padwickii, Cochliobolus miyabeanus, Drechslera australiensis [Cochliobolus australiensis], Fusarium pallidoroseum and Magnaporthe grisea were only detected from the seed coat and the endosperm, whereas Cochliobolus lunatus, Curvularia ovoidea, C. oryzae, Gibberella fujikuroi, Magnaporthe salvinii, Monographella albescens, Nigrospora oryzae [Khuskia oryzae] and Sarocladium oryzae were detected from all parts of the seed i.e. seedcoat, endosperm and embryo. Seed infection with M. salvinii resulted in seedling rot and seedling mortality. The maximum seedling mortality was found in seeds with discoloration on both the endosperm and the embryo.